1985
DOI: 10.2134/jeq1985.00472425001400010017x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Escherichia coli Through Intact and Disturbed Soil Columns

Abstract: The transport of antibiotic resistant Escherichia coli through several soils was evaluated. Up to 96% of the bacteria irrigated onto the surface of 280 mm deep intact columns were recovered in the effluent. Soil structure appeared to be related to the extent of transport. Columns prepared from mixed, repacked soil were much more effective bacterial filters than the intact soils. As rate of water input increased, the fraction of E. coli recovered in the effluent increased. The observed behavior of E. coli and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
186
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(198 citation statements)
references
References 0 publications
12
186
0
Order By: Relevance
“…Moreover, there is probability in enhancement in the penetration of the cells through the porous medium thereby leading to earlier breakthrough. The enhancement of bacterial transport at higher water flow velocity is also reported experimentally by several other investigators [7,14].…”
Section: Model Predictions and Discussionsupporting
confidence: 82%
“…Moreover, there is probability in enhancement in the penetration of the cells through the porous medium thereby leading to earlier breakthrough. The enhancement of bacterial transport at higher water flow velocity is also reported experimentally by several other investigators [7,14].…”
Section: Model Predictions and Discussionsupporting
confidence: 82%
“…Escherichia coli, poured on to intact and disturbed soil columns (Smith et al 1985), and Pseudomonas fluorescens and Bacillus subtilis introduced into the soil of field microplots (van Elsas et al 1986) were vertically transported by irrigation or water percolation. Hamdi (1970) and Wilkinson et al (1981) reported that the soil water potential affects the microbial movement in soil.…”
Section: Resultsmentioning
confidence: 99%
“…Gerba et al (1975) found that 92 to 97% of the Escherichia coli are filtered out in the first 4 cm as they move down through the soil. However, both laboratory and field studies have shown that enteric microorganisms can be transported long distances through soil (Huysman and Verstraete, 1993;Van Elsas et al, 1991;Chen, 1988;Smith et al, 1985). The explanation that has been given is the preferential flow of water transporting bacteria through soil macro pores, cracks, and fissures (McMurry et al, 1998;Abu-Ashour et al, 1994).…”
Section: Discussionmentioning
confidence: 99%